2021
DOI: 10.1080/07350015.2021.1978469
|View full text |Cite
|
Sign up to set email alerts
|

Co-citation and Co-authorship Networks of Statisticians

Abstract: We collected and cleaned a large data set on publications in statistics. The data set consists of the coauthor relationships and citation relationships of 83, 331 papers published in 36 representative journals in statistics, probability, and machine learning, spanning 41 years. The data set allows us to construct many different networks, and motivates a number of research problems about the research patterns and trends, research impacts, and network topology of the statistics community. In this paper we focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 26 publications
0
52
0
1
Order By: Relevance
“…. , 15 (say) and see which K gives the most reasonable results (e.g., Ji et al (2021a)). For either of the two normalization approaches, let R (5) , R (6) , .…”
Section: Other Score-type Post-pca Normalization Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…. , 15 (say) and see which K gives the most reasonable results (e.g., Ji et al (2021a)). For either of the two normalization approaches, let R (5) , R (6) , .…”
Section: Other Score-type Post-pca Normalization Approachesmentioning
confidence: 99%
“…This is motivated by the observation that for assortative networks, a negative eigenvalue is more likely to be spurious than a positive eigenvalue. Ji et al (2021a) found that if we use the modified SCORE with c 0 = 1, then the estimated communities are assortative (from a practical viewpoint, such a result is more appealing). For network analysis where we encounter a similar issue, we may use the modified SCORE, with the same or a different tuning parameter c 0 .…”
Section: Score* An Improvement Of Score For Assortative Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…, π n from the data matrix A. This problem has found applications in learning research interests of statisticians from co-citation networks Ji et al (2022) and understanding developmental brain disorders from gene co-expression networks Liu et al (2018).…”
Section: Introductionmentioning
confidence: 99%